Submarine structures in the Gulf of İzmit, based on multichannel seismic reflection and multibeam bathymetry - Kurt, Hülya; Yücesoy, Esra (Springer Science and Business Media LLC, 2009)
Multichannel seismic reflection and multi-beam bathymetry data were used to study the active tectonic and syn-tectonic stratigraphic setting of the Gulf of Izmit in the Marmara Sea (Turkey). The gulf and its near surroundings are deformed by the northern strand of the dextral North Anatolian Fault. Three connected basins of the gulf, the western (Darica), central (Karamursel) and eastern (Golcuk) basins are formed by active faults, as observed in the stacked and migrated seismic sections, as well as the bathymetry map. The main branch and its surrounding sedimentary strata are confined by normal faults to the north and south. These normal faults converge at depth towards the main fault, forming a negative flower structure in the gulf. The average maximum sedimentation rate is 0.4 mm/year according to the three most recent seismo-stratigraphic units that are located to the south of the main fault branch within the central basin. A 20° south-dipping major discontinuity along the northern shoreline of the gulf represents the top of Paleozoic basement.